Estudos comparativos de dietas comerciais extrusadas utilizadas na alimentação de juvenis de tambaqui, Colossoma macropomum Cuvier 1818, em pré-cultivo - Sousa, Daury Gabriel de (2001)
The tambaqui, Colossoma macropomum, is a native species of the Solimões-Amazonas, Orinoco rivers and their tributaries, acclimatized in the Northeast of Brazil by the Departamento Nacional de Obras Contra as Secas (DNOCS) and which has been used in the population of dams and rivers and in cultivation in nurseries, with excellent results. The objective of this research was to test extruded isoprotein feeds (32% crude protein), from the brands Purina, Aqualine from Supra, Proaqua from Nutron and Friaqua from Fri-Ribe, comparing their efficiency for juvenile tambaqui, based on the following parameters: growth in length and weight, average weight gain, biomass, feed conversion and survival, in crops lasting 110 days, with a view to reducing the cultivation time in the nursery, which currently revolves around 12 months. This work was carried out at the Rodolpho von Ihering Ichthyological Research Center (Pentecoste, Ceará, Brazil), at DNOCS. A total of 1,080 fry were used (3 individuals/m2), with initial average length and weight of 13.52 cm and 38.92 g, respectively. To evaluate growth efficiency in length and weight, the following were calculated: (1) average net weight gain (GMP) and (2) average weight gain per day (GMPD), both expressed in grams; (3) feed conversion; (4) initial biomass and (5) final biomass, both expressed in kilograms. Growth in length and weight, at the end of the experiment, did not show a statistically significant difference at the 5% level, considering that all rations tested had the same crude protein content. Daily weight gains were 2.11, 2.07, 1.94 and 1.78 g/day for the Friaqua, Purina, Aqualine and Proaqua, respectively, which also did not show a statistically significant difference at the level of 5%. After 110 days of cultivation, the total biomass values were 290,704.5g, 252,616.5, 252,531.9 g and 232,531.9 g, respectively for the Friaqua, Purina and Proaqua and Aqualine. Total feed consumption, during the studied period, varied approximately from 126 to 148 kg. Feed conversions were 2.16:1, 2.19:1, 2.32:1 and 2.50:1 for Purina, Aqualine, Friaqua and Proaqua, respectively. The values of the coefficients of determination (R2) for the relationships total length/days of cultivation and total weight/days of cultivation were greater than 0.95. The survival of tambaquis, at the end of 110 days of cultivation, was higher for the Friaqua (91.5%) and lower for the Aqualine (67.8%). The possibility of reducing the cultivation period from 12 to 8 months would allow three production cycles to be carried out in 24 months, which would represent a huge gain for fish farmers.